Estado do conhecimento sobre línguas bantu e educação bilíngue em Moçambique, 2017-2022 - Lino, Cesário Lopes Manuel Nunes (2024)
This dissertation is an in-depth exploration of academic research on the teaching of Bantu languages and bilingual education in Mozambique, conducted in both Brazil and Mozambique. The study critically examines theses, dissertations, and academic articles from 2017 to 2022, with the aim of analyzing scientific production related to Bantu languages and Mozambican bilingual education. Utilizing the State of Knowledge methodology (Morosini, Santos, Bittencourt, 2021), the study systematically maps academic works, highlighting their focuses, methodologies, and results. The findings reveal a growing recognition of Bantu languages in Mozambican scientific research, indicating a positive acknowledgment of these languages. However, political and social challenges are identified that need to be addressed for these languages to play a more significant role in society. Concerning bilingual education, there is skepticism about the current model, primarily due to the lack of human, material, and financial resources. Nonetheless, many view the model as a promising avenue for cultural and social inclusion. Additionally, bilingual education is considered a potential strategy to enhance access to education and promote the development of Mozambican languages, thereby contributing to educational quality and the strengthening of cultural identity in Mozambique.